Manufacture of cement-gypsum board using core-kenaf (Hibiscus cannabinus L.) with curing autoclave technology - Rohny Setiawan Maail (Forest Research Institute Malaysia, 2015)
Cement and gypsum bonded lignocellulosic fiber reinforced materials will ultimately become the ideal ecological building products. The ability to use industrial co-products and wastes as in their matrix material makes it an environmentally sustainable product. The objective of this study was to evaluate the effect of cement-gypsum proportions and curing times on the properties of the cement gypsum board with kenaf core. Three levels of proportion cement and gypsum were used i.e. 40:60, 50:50 and 60:40, where cement was used as face-back layers and gypsum was used in the core layers. Five levels of curing time were used i.e. control 2, 4, 8 and 16 hours. Calcium chloride (CaCI2) 3% and 2% borax was used as an accelerator and retarder. The physical and mechanical properties of cement-gypsum board were tested according to JIS A 5417-1992. Results show that the proportion cement 60 and gypsum 40 with curing time of 8 hours yield the properties of cement-gypsium boards fulfilling all examinations parameters of JIS A 5417 standard. The curing process was found to be better than conventional curing time of 2 weeks.